2019
DOI: 10.1186/s40168-019-0667-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of human Lactobacillus crispatus isolates reveals genes for glycosylation and glycogen degradation: implications for in vivo dominance of the vaginal microbiota

Abstract: Background A vaginal microbiota dominated by lactobacilli (particularly Lactobacillus crispatus ) is associated with vaginal health, whereas a vaginal microbiota not dominated by lactobacilli is considered dysbiotic. Here we investigated whether L. crispatus strains isolated from the vaginal tract of women with Lactobacillus- dominated vaginal microbiota (LVM) are pheno- or genotypically distinct from L.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 50 publications
7
99
1
2
Order By: Relevance
“…Pullulanase is an enzyme that breaks down glycogen [14]. In the vagina, glycogen is the main source of carbohydrates for microorganisms [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pullulanase is an enzyme that breaks down glycogen [14]. In the vagina, glycogen is the main source of carbohydrates for microorganisms [47].…”
Section: Discussionmentioning
confidence: 99%
“…The vaginal niche in a dysbiotic state was under some immune pressure. The GTs regulated the surface glycogen of L. crispatus through a phase change, helping it escape immunity [14].…”
Section: Introductionmentioning
confidence: 99%
“…The human vaginal tract, lined with multiple layers of stratified squamous epithelial cells (Anderson et al, 2014) and heavily regulated by the fluctuation of estrogen hormones (Farage and Maibach, 2006), is acidified to pH 3.5-4.5 mainly by lactic acid produced by the commensal microbiota (Boskey et al, 2001). With secretion of α-amylase from the host, the commensal bacteria in the vaginal tract are presumably able to utilize glycogen as a carbon source, the main carbohydrate stored in the superficial and intermediate layer of the epithelial cells and released when epithelial cells die and slough off (Anderson et al, 2014;Spear et al, 2014;van der Veer et al, 2019). On the other hand, the human GI tract is comprised of a single layer of columnar epithelial cells coated by a thick layer of mucus secreted by goblet cells (Turner, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…O'Flaherty et al (2018 reported that lactobacilli containing bile salt hydrolase (BSH) proteins are usually associated with vertebrate-adapted lifestyle rather than environmental and plant-associated lifestyle. Possible mechanism for L. crispatus to dominate vaginal tract has been suggested as the presence of glycogen degradation genes in their genomes (van der Veer et al, 2019). Others have investigated if specific proteins exist among vaginal species allowing vaginal specialization (Mendes-Soares et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, selection of candidate probiotic strains seems to be their ability to adhere to vaginal cells and produce lactic acid and hydrogen peroxide (Hemmerling et al, 2009). Genomic and metabolomic studies have shown that there are significant differences between L. crispatus strains (van der Veer et al, 2019; Watson et al, unpublished), so some selection criterion is needed before expecting a strain to be effective. If the species is so protective, why is it apparently readily displaced by anaerobes?…”
Section: Too Much Emphasis On Community State Types and Not Enough Onmentioning
confidence: 99%